Roitt's essential immunology - Delves, Peter J.; Roitt, Ivan M. (Ivan Maurice) (Essentials (Wiley-Blackwell), 2011)
"A new, 12th edition of the definitive Immunology textbook, now fully up-to-date on the latest knowledge and concepts about the workings of the immune system. Essential Immunology is a perfect course textbook to support a series of lectures, or themes, on Immunology: pedagogy has been strengthened throughout, and the text is now fully supported by a suite of online resources as well as a FREE enhanced Wiley Desktop Edition"--Provided by publisher.